Pengembangan E-LKPD Berbantuan Liveworksheet untuk Meningkatkan Hasil Belajar pada Materi Aku dan Kebutuhanku - Adelia Najwa Hafiz; Yuli Mulyawati; Nurhikmah (Mataram University, 2026)
This study was motivated by the results of observations and interviews, which indicated that fourth-grade students at SDN Depok had low cognitive learning outcomes, particularly in the skills of analyzing and evaluating, in the Natural and Social Sciences (IPAS) subject on the topic Me and My Needs. This condition was influenced by the limited active participation of students during the learning process. This study aimed to develop a Liveworksheet -assisted electronic student worksheet (E-LKPD), examine its feasibility, and evaluate its effectiveness in improving students' learning outcomes. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and Evaluation stages. The participants were 23 fourth-grade students of SDN Depok. Data were collected through observations, interviews, validation questionnaires, and learning achievement tests. The results showed that the Liveworksheet -assisted E-LKPD was categorized as highly feasible, with validation scores of 98% from the media expert, 100% from the language expert, 94% from the subject matter expert, and 96% from the classroom teacher. The effectiveness test showed that the average pre-test score increased from 52.61 to 88.04 on the post-test, with an N-Gain score of 75.87%, which falls into the high category, particularly in students' cognitive abilities to analyze and evaluate after using the E-LKPD. Based on these findings, it can be concluded that the Liveworksheet -assisted E-LKPD is highly feasible and effective in improving students' learning outcomes on the topic Me and My Needs. The product also offers an attractive design, is easy to use, and supports a more interactive learning process.